Patients’ knowledge and perception on anaesthesiologist and anaesthesia - Nanyan, Suhaila; Johari, Mohamad Fariz; Holid, Mohamad Nazrin; Othman, Usamah (International Islamic University Malaysia, 2018)
Anaesthesiologists play vital roles in perioperative patients’ care and chronic pain management. However, not many patients are aware of the role of anaesthesiologists. We aimed to measure the level of patients’ knowledge regarding the role of anaesthesiologist and anaesthesia